Herbal Medicine for Hypertension: Literature Review - Sari, Putri Irwanti; Martawinarti, RTS Netisa; Mutmainnah, Muthia; Meinarisa, Meinarisa; Mekeama, Luri; Yusnilawati, Yusnilawati; Mawarti, Indah; Putri, Musiya Ramadhani (Universitas Jambi, 2024)
Hypertension is a medical condition that often requires long-term management to reduce the risk of cardiovascular disease. Herbal therapy has become an intriguing focus of research in seeking effective and sustainable alternatives in lowering blood pressure. This literature review presents an analysis of seven scientific journals focusing on herbal therapy for hypertension. The study employs a Literature Review method by gathering articles from relevant journals. The review findings indicate that various herbal therapies, ranging from garlic combination herbal medicine, rosella flower decoction, green tea consumption, education on the use of gotu kola and turmeric leaves, to cucumber juice therapy, bay leaf, and papaya juice, have the potential to lower blood pressure in hypertensive patients. The mechanisms of action of these herbs vary, including vasodilator, anti-inflammatory, and antioxidant effects. Based on the review of the seven published journals, it can be concluded that non-pharmacological therapy plays a significant role in hypertension treatment. These journals highlight the importance of considering comprehensive and individualized treatment options when managing hypertensive patients. Although the research methods vary, the results consistently indicate significant benefits of non-pharmacological treatment. However, further research is needed to validate these findings and expand our understanding of the efficacy and mechanisms of non-pharmacological treatments.